The Influence of Principal’s Managerial Competence, Teachers’ Pedagogical Competence, and The Utilization of Educational Facilities on The Effectiveness of Learning Management in Primary Schools across South Amfoang District, Kupang Regency: Pengaruh Kompetensi Manajerial Kepala Sekolah, Kompetensi Pedagogik Guru, dan Pemanfaatan Fasilitas Pendidikan terhadap Manajemen Pembelajaran Efektif di Sekolah Dasar se Kecamatan Amfoang Selatan, Kabupaten Kupang - Septiani Yeni Mere; Priadi Surya (Borneo Educational Journal (Borju), 2026)
Abstract This study aims to analyze the association between the principal's managerial competence, teachers' pedagogical competence, and the utilization of educational facilities with the effectiveness of learning management in primary schools across South Amfoang District, Kupang Regency. Adopting a quantitative correlational design, the study involved 96 teachers as respondents selected through a census technique. Data were collected via questionnaires and analyzed using multiple linear regression. The findings reveal a statistically significant positive relationship, with teachers' pedagogical competence emerging as the most prominent predictor. Although the Adjusted R² value reached 0.936, these findings should be interpreted with caution due to potential multicollinearity and response bias inherent in perception-based survey data within a homogeneous sample. The results suggest that in peripheral areas, the integration of human capacity and physical resources tends to operate simultaneously in supporting learning effectiveness. This study recommends the necessity of strengthening pedagogical competencies that are contextualized to the infrastructure constraints in underdeveloped regions.   Abstrak Penelitian ini bertujuan untuk menganalisis asosiasi antara kompetensi manajerial kepala sekolah, kompetensi pedagogik guru, dan pemanfaatan fasilitas pendidikan dengan efektivitas manajemen pembelajaran di sekolah dasar se-Kecamatan Amfoang Selatan, Kabupaten Kupang. Menggunakan pendekatan kuantitatif korelasional, penelitian ini melibatkan 96 guru sebagai responden melalui teknik sensus. Data dikumpulkan dengan instrumen kuesioner dan dianalisis menggunakan regresi linear berganda. Hasil menunjukkan adanya hubungan positif dan signifikan secara statistik di mana kompetensi pedagogik guru muncul sebagai prediktor yang paling menonjol. Meskipun nilai Adjusted R² menunjukkan angka 0,936, temuan ini harus diinterpretasikan secara hati-hati mengingat adanya potensi multikolinearitas dan bias persepsi dalam data survei di wilayah dengan karakteristik sampel yang homogen. Hasil ini mengindikasikan bahwa di wilayah pinggiran, integrasi kapasitas manusia dan sumber daya fisik cenderung bergerak simultan dalam mendukung efektivitas pembelajaran. Peneliti merekomendasikan perlunya penguatan kompetensi pedagogik yang kontekstual dengan keterbatasan sarana di daerah tertinggal.